Attention for the Inattentive: Positive Effects of Negative Financial Shocks - Ouimet, Paige; Tate, Geoffrey (Review of Finance, 2020)
Abstract Using unique data on employee ownership plans, we find that negative shocks lead to changes in portfolio choices among previously inattentive investors. Employees within employee ownership plans did not actively select into ownership, but instead received grants upon employment. Many employees remain initially passive within these plans. However, following the 2008 Financial Crisis, they become more likely to exercise options, sell restricted stock, and participate in an Employee Stock Purchase Plan (ESPP). These changes likely improve welfare. For example, nonparticipation in an ESPP leaves money on the table. Our results improve our understanding of how investors’ personal return experiences affect investment choices. Negative shocks can increase attention among previously passive investors, yielding decisions that are closer to the optimum.